From green to brown: two decades of darkening coastal water in the Gulf of Riga, the Baltic Sea - Aigars, Juris; Suhareva, Natalija; Cepite-Frisfelde, Daiga; Kokorite, Ilga; Iital, Arvo; Skudra, Māris; Viska, Maija (Frontiers in Marine Science, 2024)
Over the past decades, changes in the light conditions of coastal waters, induced by darkening due to water browning, has been gaining momentum within the scientific community. Although there is a general agreement that the darkening of coastal water is caused by shifts in climatic conditions, the actual links between trends in light attenuation caused by water browning and drivers are still being debated, as causality relationships are often assessed through the use of indirect evidence. In this study, we employed algorithmically processed remote-sensing and modelled data with substantially higher resolution than in-situ data as well as in-situ data. Two decades (1998-2007 and 2008-2018) were compared to test impact of parameters known to be altered by climate change, such as freshwater runoff, mobilization of soil dissolved organic carbon, and alteration of freshwater-saline water balance in coastal waters, on darkening of coastal waters of the Gulf of Riga, Baltic Sea. The study results indicated that the most likely cause of the observed darkening of coastal waters in the study region was the mildening of winter conditions. At the same time, the study results highlighted the urgent need for detailed, time-sensitive data, since none of the conclusions drawn from the analyses of available data were unequivocal.